Alterações neonatais e maternas relacionadas ao óbito infantil em crianças com gastrosquise - Coelho, Amanda Santos Fernandes (2015)
Infant mortality is an important indicator of a country’s health. It is observed in several regions of the world a proportion of deaths attributable to congenital malformations. Worldwide, it is estimated that prevalence occurs in 9% of live births. Among the major abnormalities is gastroschisis, that is a congenital malformation in which there is an exteriorization of the viscera through the abdominal wall defect to the right of the umbilical cord, which is implanted in its normal position. The objective of this study was analyze the neonatal and maternal changes related to infant mortality in children with gastroschisis. This is a cross-sectional and retrospective study with a quantitative approach. It used for analysis, secondary data collected from medical records of patients treated at a public hospital in Goiânia-GO, from 2004 to 2014. The study included 123 patients diagnosed with gastroschisis, which met the criteria adopted. In relation to maternal variables, 57.7% of the women were younger than 20 years, 64.2% were first pregnancy, cesarean birth occurred in 65% of cases, there was an average of 4.8 ± 2.5 prenatal consultation. In relation to neonatal variables, 59% of the new born with gastroschisis were male. The gestational age at birth of the 123 pregnancies ranged from 29.4 to 40.4 weeks (average = 36.5 ± 1.8 weeks). The weight of the new born ranged from 890g to 3800g (average = 2351 ± 474,2g), the average of the Apgar index in the first minute was 6.6 ± 1.8. Associated malformations (not intestinal) were found in 10 (8.1%) patients and 17 (13.8%) patients had intestinal abnormalities, and at this last the most common was the intestinal atresia. By observing the eviscerated organs, 70.7% of patients had only exposed intestinal loops and about other herniated organs, the stomach has been externalized in 27.6% of cases. The general mortality rate was 41% of cases. Statistically significant association was observed between the occurrence of death and mothers who performed less monitoring in prenatal care (p = 0.027) and when there was no diagnosis of gastroschisis in prenatal care (p = 0.001). It was also observed statistically significant association between the occurrence of death and the presence of complex gastroschisis (p = 0.032) and herniation of other organs beyond just the intestine (p = 0.018). It is concluded that, in relation to maternal and neonatal profile of gastroschisis, the condition has no gender preference, particularly affecting children of young first-time mothers. Perinatal mortality of gastroschisis in this analysis seems to depend mainly on the reduced prenatal care, the absence of prior diagnosis at birth, the presence of complex gastroschisis and herniation of other organs than just the intestine.